Familial ATTR amyloidosis: microalbuminuria as a predictor of symptomatic disease and clinical nephropathy - Lobato, L. (2011)
Familial ATTR amyloidosis: microalbuminuria as a predictor of symptomatic disease and clinical nephropathy. Lobato L, Beirão I, Silva M, Bravo F, Silvestre F, Guimarães S, Sousa A, Noël LH, Sequeiros J. SourceDepartment of Nephrology and Centro de Estudos de Paramiloidose, Hospital Geral de Santo António and Institute for Molecular and Cell Biology, Porto, Portugal. llobato@netcabo.pt Abstract BACKGROUND: Portuguese type familial amyloid polyneuropathy (FAP) is a neuropathic amyloidosis caused by a mutant transthyretin (TTR). Varying degrees of renal involvement have been reported. Our aim was to assess the value of microalbuminuria (MA) for predicting clinical neurological disease and overt nephropathy in TTR-related amyloidosis. METHODS: All subjects had the TTR Val30Met mutation, and were recruited between 1993 and 1999. We have prospectively evaluated 22 asymptomatic gene carriers (7 male, 15 female; mean age 41.6+/-9.6 years) and 32 patients with neuropathy (14 male, 18 female; 36.8+/-8.8 years, on average, 33.0+/-9.3 years at the onset of neuropathy). We measured urinary albumin excretion every year, if asymptomatic, or every 6 months if already affected. Kidney biopsies were performed in patients with normal urinary albumin excretion, MA, and overt nephropathy, respectively. RESULTS: In asymptomatic carriers, persistent MA was detected in eight (36%) subjects. The presence of MA in asymptomatic gene carriers, compared with those having normal urinary albumin excretion, conferred a 4.8-fold risk of developing neuropathy, usually within the subsequent 3 years. Once neurological signs appeared, nephropathy, manifested as MA, progressed to overt nephropathy in one-half of subjects. In patients with neuropathy, 24 (75%) had MA during follow-up: evolution towards clinical renal disease occurred in 14 (58%) and renal failure occurred in five (21%), always after a course of MA. Proteinuria or renal failure without prior persistent MA were never observed in the present patient cohort. Histopathological evaluation did not reveal glomerular lesions other than amyloid deposits to explain abnormal urinary albumin excretion. The amount of mesangial and vascular-pole amyloid deposits was correlated with the degree of albuminuria. CONCLUSIONS: Microalbuminuria represents the first stage of clinical TTR amyloid nephropathy and is premonitory of neuropathy. Its presence identifies a subgroup of patients who are more prone to develop overt nephropathy. Screening of MA may be important to assess disease onset and to recommend liver transplantation in individuals at risk.